Discovery of rimonabant and its potential analogues as anti-TB drug candidates - Gajbhiye, J. M.; More, Namita A.; Patil, Manoj D.; Ummanni, R.; Kotapalli, S. S.; Yogeeswari, P.; Sriram, D.; Masand, Vijay H. (Medicinal Chemistry Research, 2015)
Rimonabant and its analogues have been synthesized in moderate to good yields using a simple synthetic route. All the newly synthesized compounds were subjected to in vitro screening against M. tuberculosis and M. smegmatis. The most potent analogue JMG-14 exhibits MIC value of 3.13 compared to 3.25 and 50 A mu g/ml for ethambutol and pyrazinamide, respectively. The molecular docking reveals that pyrazole ring, number and position of halogen atoms play a crucial role in deciding interactions with MTCYP-121. These findings open up a new avenue in the search of potent anti-TB drugs with rimonabant and its novel analogue JMG-14 as lead molecules.
Keywords: Diaryl pyrazoles; H37Rv; MTCYP-121; Mycobacterium tuberculosis; Rimonabant; tuberculosis

Molecular docking and QSAR analyses for understanding the antimalarial activity of some 7-substituted-4-aminoquinoline derivatives - Shibi, I. G.; Aswathy, L.; Jisha, Radhakrishnan S.; Masand, Vijay H.; Divyachandran, A.; Gajbhiye, J. M. (European Journal of Pharmaceutical Sciences, 2015)
The quinoline moiety is one of the widely studied scaffolds for generating derivatives with various pharmacophoric groups due to its potential antimalarial activities. In the present study, a series of 7-substituted-4-aminoquinoline derivatives were selected to understand their antimalarial properties computationally by molecular modeling techniques including 2D QSAR, comparative molecular field analysis (CoMFA), comparative molecular similarity indices analysis (CoMSIA) and molecular docking. The 2D-QSAR model built with four descriptors selected by genetic algorithm technique and CoMFA model showed satisfactory statistical results (Q(2) = 0.540, R-ncv(2) = 0.881, F value = 157.09). A reliable CoMSIA model out of the fourteen different combinations has a Q(2) value of 0.638. The molecular docking studies of the compounds for 1CET as the protein target revealed that ten compounds showed maximum interactions with the binding site of the protein. The present study highlights the unique binding signatures of the ligands within the active site groove of the target and it explains the subtle differences in their EC50 values and their mechanism of inhibition. (C) 2015 Elsevier B.V. All rights reserved.

Efficient synthesis of potent anti-tubercular drug candidate BM212 - More, N. A.; Patil, M. D.; Garud, D. R.; Gajbhiye, J. M. (Rasayan Journal of Chemistry, 2016)
A novel five step total synthesis route for an anti-tubercular drug BM212 starting from 4-chlorophenacyl bromide was developed with 48% overall yield. The synthesis is amiable for the synthesis of biologically active derivatives of BM 212.

Convenient synthesis of the enantiomerically pure (S)-2,4-dihydroxybutyl-4-hydroxybenzoate using hydrolytic kinetic resolution - More, N. A.; Jadhao, N. L.; Garud, D. R.; Gajbhiye, J. M. (Synthetic Communications, 2018)
(S)-2,4-Dihydroxybutyl-4-hydroxybenzoate was prepared in an extremely simple and practical way with high enantiomeric excess (99% ee) using Jacobsen’s Hydrolytic Kinetic Resolution technique as a key step and source of chirality.